Advanced separation technologies for oil/water blends: A study on PVC/PS/SWCNT nanocomposite membranes - Fatima Fahim Ouda; Salih Abbas Habeeb (Desalination and Water Treatment, 2025)
Streamline the abstract to focus on the main objectives, methodology, and key outcomes. Highlight the novelty of the PVC/PS/SWCNT nanocomposite and its environmental relevance. Membranes were fabricated with optimized PVC/PS blend ratios (25:75, 50:50, 75:25) and SWCNT loadings (0.1–0.4 wt%). Morphological analysis via FE-SEM revealed that SWCNT incorporation reduced the average fiber diameter from 96.61 ± 34.46 nm to 43.58 ± 11.58 nm while increasing the BET surface area to 3.21 m²/g (0.1 % SWCNT) and pore volume to 0.0041 cm³ /g. FTIR and XRD analyses confirmed successful SWCNT dispersion, enhancing crystallinity (33.33 % vs. 26.31 % for the pure blend) and thermal stability, with the glass transition temperature (Tg) rising to 83.89°C. The nanocomposite membranes exhibited exceptional separation performance, achieving a maximum flux of 40,000 L/m²h and 96.73 % crude oil rejection at 300 mg/ L. Rejection efficiency (Re%) varied with oil concentration from 45.56 to 89.3 mg/ L were 45.56–70.23 % by M-75 for aromatic compounds. Moreover, rejection efficiency (Re%) varied with oil concentration from 35.55 mg/ L to 9.8 mg/ L were 64.45–96.73 % by M1 for aromatic compounds. Flux decline ratios increased with concentration and cycles (e.g., 4.2–7.3 % for blends vs. 6.8–14.2 % for SWCNT composites at 300 mg/L oil), reflecting fouling resistance. UV-Vi’s spectroscopy and cyclic tests validated stability, with surface properties (e.g., contact angle 128° to 111.15°) tailored by SWCNT loading. Notably, the membranes exhibited consistent performance under industrial wastewater conditions, demonstrating their effectiveness in reducing oil pollution. These findings highlight their potential as scalable, sustainable solutions for wastewater treatment, combining high efficiency with lower operational costs compared to conventional methods.